Detection frequency and duration of circulating antiphospholipid syndrome markers in patients with verified COVID-19 - Yu. V. Mikhailova; N. V. Chepurchenko; A. P. Obriadina (IRBIS LLC, 2024)
Aim: to develop enzyme-linked immunosorbent tests for assessing the antiphospholipid syndrome (APS) markers and determine prevalence of three antiphospholipid antibody (aPL) types at different COVID-19 stages.   Materials and Methods. A comparative longitudinal controlled study was conducted by examining 120 subjects with COVID-19 diagnosis verified by reverse transcription polymerase chain reaction. Donor serum samples collected before November 2019 were used as a control group. The laboratory study included measurement of IgA, IgM and IgG against β2-glycoprotein 1 (β2-GP1), cardiolipin, phosphatidylserine-prothrombin complex (PS-PT) by using domestically produced test systems based on indirect two-step enzyme-linked immunosorbent assay.   Results. Validation of the developed experimental tests was carried out in comparison with foreign commercial analogues in accordance with international standards. Alternative antigenic targets for effective diagnosis of antibodies against β2-GP1 were studied. Analyzing rate of aPL in patients at different COVID-19 stages showed that in acute vs. convalescence stage it was higher by 1.3-fold (81.7 and 65.0 %, respectively). The first rank detection place was assigned to IgG against β2-GP1, cardiolipin and PS-PT, the second - IgM against cardiolipin. The profile of the detected antibodies changed at various COVID-19 stages driven by time frame elapsed from the moment of diagnosis.   Conclusion. Recombinant constructs are created and analytical conditions are optimized for determining various aPL types. It was shown that along with other viral infections, COVID-19 triggers autoantibody production demonstrating that 54.2 % individuals infected with SARS-CoV-2 were positive at least for one autoantibody type. The majority of such virus-associated aPL are presumably transiently positive.